Evaluasi Pelaksanaan Peraturan Penetapan Standar Jasa Profesi Apoteker di Daerah Istimewa Yogyakarta - Ingenida Hadning; Bangunawati Rahajeng; Pinasti Utami; Siti Martini Khairiati; Noviya Wardhani; Nuariska Laila Ramadhani; Nanang Munif Yasin (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice), 2022)
The small salary received by pharmacists is one of the reasons for the low attendance of pharmacists in pharmacies. The regional management of the Yogyakarta Special Region of Indonesian Pharmacist Association (PD IAI DIY) has issued a Decree (SK) on Professional Service Standards for Pharmacists in DIY in 2017 so that it can be used as a reference for pharmacists in Yogyakarta who practice in pharmacies. This study aims to determine the implementation of the decree on pharmacists in DIY. Research variables are basic services, additional income and other facilities. The research instrument is a questionnaire. The sampling method used is accidental sampling. To calculate the number of samples used the Slovin formula. With a confidence level of 90%, the minimum sample size is 222 respondents. However, in this study, 268 pharmacists who practice in pharmacies finally obtained respondents. Respondents came from five districts/cities in DIY. Data were collected from August 2019 to February 2020. The research instrument used an e-questionnaire on a google form which was distributed through social media for members of IAI DIY and also distributed directly to several pharmacies in DIY. The data obtained were analyzed through descriptive statistical tests. The results showed that only 11 respondents met all the criteria in the SK. In the category of pharmacists who hold SIA, only seven respondents met all the criteria in the SK, namely three respondents from Sleman, two respondents from Yogyakarta City, and two respondents from Bantul. In the non-SIA pharmacist category, only four respondents met all the criteria in the SK, namely one respondent from Sleman, two respondents from Yogyakarta City, and one respondent from Gunung Kidul. It can be concluded that the SK PD IAI DIY regarding professional service standards has not been fully implemented by DIY pharmacists.